Pengaruh Edukasi Gizi Terhadap Feeding Practice Ibu Balita Stunting Usia 6 – 59 Bulan di Wilayah Kerja Puskesmas Biaro Kabupaten Agam Tahun 2024 - Gita Rahmadani; Sonia Wulan Dari (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2025)
Currently, the issue of stunting in toddlers remains quite high and can be triggered by poor feeding practices. According to the Biaro Health Center report in 2022, of the 3,036 toddlers, 172 (5.67%) were stunted. In 2023, from 3,096 toddlers, the number of stunted children increased to 227 (7.33%). The purpose of this study was to determine the effect of nutrition education on the feeding practices of mothers with stunted toddlers aged 6 – 59 months in the working area of Puskesmas Biaro, Agam Regency in 2024. This study is a pre-experimental research with a pretest-posttest one-group design. The research was conducted from August to December 2024 in the Biaro Health Center working area. The population of this study was all mothers of stunted toddlers aged 6 – 59 months in October 2024 in the Biaro Health Center working area, totaling 39 individuals, with a sample size of 16. Sampling was done using purposive sampling. Data were collected using questionnaires and analyzed with univariate and bivariate analysis using paired t-test. The results showed that the average feeding practice score of mothers with stunted toddlers aged 6 – 59 months before nutrition education was 35.0 with a standard deviation of 5.657, and after the education, it was 49.94 with a standard deviation of 4.864. The statistical test results indicated a significant effect of nutrition education on the feeding practices of mothers with stunted toddlers aged 6 – 59 months, with a p-value of 0.000 (p < 0.05). The conclusion is that nutrition education has an effect on the feeding practices of mothers with stunted toddlers aged 6 – 59 months. It is recommended that health workers provide routine nutrition education to improve the feeding practices of mothers with stunted toddlers.